Pandemic Impact of Covid-19 in The New Normal Area on Consumer Behaviour - Nawangsih Nawangsih (Jurnal Ilmu Manajemen Advantage, 2021)
The research objectives are: to find out the positive and negative impacts of the Covid-19 pandemic in the new normal era on the shift in consumer behavior and identify types of potential new business opportunities to be developed in the current new normal era. The research method uses this type of research based on literature study. The results of research based on literature studies show that: consumers make scale and value a priority in making purchases, the pandemic creates a new economy based on work from home, service changes, digital marketing, product diversification, wise consumption, fosters a sense of solidarity, family togetherness, creativity and innovation, careful activities, opportunities to increase knowledge and love for local and domestic products. The sectors affected by the pandemic are generally the prima donnas, the occurrence of punic buying and ease of service, a decrease in sales turnover and a shift in consumption patterns from offline to online. Meanwhile, new business opportunities that can be developed include: digital-based creative and innovative businesses, healthy and healthy culinary businesses, and several other potential businesses.